Pengaruh Penggunaan Teknologi Big Data dan Efisiensi Operasi Terhadap Kinerja Keuangan Perusahaan Perbankan - Nugroho Nurdhianto (Transpublika Publisher, 2025)
The development of technology, especially Big Data, has brought significant changes in the banking industry by enabling the optimisation of risk analysis, increased operational efficiency, and more accurate decision-making. However, the impact of the application of Big Data on the financial performance of banks in Indonesia has not been widely studied empirically. This study aims to analyse the effect of the use of Big Data technology and operational efficiency on the financial performance of banks in Indonesia. Using a quantitative approach, this study processes secondary data from the annual reports of 12 banks classified as Core Capital Bank Group (KBMI) 3 during the period 2021-2023. The independent variables in this study include the application of Big Data and operational efficiency as measured by the ratio of operating expenses to operating income (BOPO), while financial performance is measured using the CAMEL method. The data was analysed using multiple linear regression after going through a series of classical assumption tests. The results show that although the adoption of Big Data in the banking sector has increased in recent years, it has not had a significant impact on the financial performance of banks. Similarly, operational efficiency as measured by BOPO does not have a significant relationship with financial performance. Overall, the findings indicate that other factors, such as capital policy, risk management, and regulation, have a more dominant influence on banks' financial stability and performance.